2013
DOI: 10.1097/01.ncn.0000432127.99644.25
|View full text |Cite
|
Sign up to set email alerts
|

Features of Computerized Clinical Decision Support Systems Supportive of Nursing Practice

Abstract: This study aimed to organize the system features of decision support technologies targeted at nursing practice into assessment, problem identification, care plans, implementation, and outcome evaluation. It also aimed to identify the range of the five stage-related sequential decision supports that computerized clinical decision support systems provided. MEDLINE, CINAHL, and EMBASE were searched. A total of 27 studies were reviewed. The system features collected represented the characteristics of each category… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
24
0
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(30 citation statements)
references
References 21 publications
5
24
0
1
Order By: Relevance
“…[33] Moreover, PCC is grounded from an ethical perspective [10] that is in line with the code of ethics for nurses, [6] PCC is one way to promote health, prevent illness and alleviate suffering that is in line with people's rights and self-determination (i.e., to adapt to patient's needs, resources and conditions). [1,2,4] The results of the present study show that care plans need conditions for patient involvement by using simple everyday language and a systematic visible structure in medical records that harmonizes with earlier research; [16,19,34] these studies point out that IT support and teamwork are crucial aspects. Moreover, support of an ethical approach that forms the basis of PCC [1,2,11] can guide and improve teamwork for all involved parties (staff, patient, and relatives) using all available resources, including patients.…”
Section: Discussionsupporting
confidence: 80%
See 1 more Smart Citation
“…[33] Moreover, PCC is grounded from an ethical perspective [10] that is in line with the code of ethics for nurses, [6] PCC is one way to promote health, prevent illness and alleviate suffering that is in line with people's rights and self-determination (i.e., to adapt to patient's needs, resources and conditions). [1,2,4] The results of the present study show that care plans need conditions for patient involvement by using simple everyday language and a systematic visible structure in medical records that harmonizes with earlier research; [16,19,34] these studies point out that IT support and teamwork are crucial aspects. Moreover, support of an ethical approach that forms the basis of PCC [1,2,11] can guide and improve teamwork for all involved parties (staff, patient, and relatives) using all available resources, including patients.…”
Section: Discussionsupporting
confidence: 80%
“…[23,45] One suggestion is to include both teaching and examination-based elements focused on documentation of care plans supported by computerized clinical nursing practice support systems. [34] This goal is expressed in terms of skill and the ability to plan orally and in written report form and to discuss measures and treatment results with interested parties in accordance with relevant regulations, routines, best practice and so on. However, nurses' experiences with obstacles during work make it difficult for them to plan, document and update care plans in a manner that ensures patient safety.…”
Section: Discussionmentioning
confidence: 99%
“…40 However, fewer published studies 4143 have been assessments of attitudes and perception toward clinical alerts and CDS systems. Feblowitz et al 44 found that among health care providers, alert acceptance was 38.1% (interquartile ratio, 14.8%–54.4%), indicating the mass complexities of alerts.…”
Section: Discussionmentioning
confidence: 99%
“…The nurses had frequently expressed the advantages of the CDSS both for themselves and the patients as identified in the literature (Ahmadian et al., ; Anderson & Wilson, ; Lee, ). Randell and Dowding () listed the factors affecting the success of the decision support system as the system properties, ongoing training, and supportive environment.…”
Section: Discussionmentioning
confidence: 99%